Model Pengembangan Puri Agung Karangasem Sebagai Daya Tarik Wisata Budaya Bali (Jurnal Ilmiah Pariwisata; Vol 19 No 1 (2014), 2014)
Puri Agung Karangasem Amlapura previously known as Castle or Castle Kangingan. The castle functioned as the residence of the king after king of Karangasem already under the influence of the Netherlands which at the time Anak Agung Gde Jelantik appointed stedehouder Development I. Puri Agung Karangasem unique enough to be studied, considering the castle is a castle building and naming space adapted from European countries. This happens because at the time of construction and development, in collaboration with the Dutch king. However, despite the unique views of aspects of the building and its history, this castle looks less attractive evident from the lack of tourists visiting. Recognizing this, the study of Puri Agung Karangasem was done with the aim of producing a model development Puri Agung Karangasem as a cultural tourist attraction. In this paper the potential and Puri Agung Karangasem development model described in hopes into consideration for the castle in developing himself as one of the cultural attractions in Karangasem regency.
Keywords: Puri Agung Karangasem, Model, Development, Tourist Attractions, Culture